STRATEGI PROMOSI PERIKLANAN YANG EFEKTIF - Ramsiah Tasruddin (Jurnal Al-Khitabah, 2015)
“Dreadful of advertisement magic have pushed the strength go into effect the hegemony marketing for advertiser company. Even sometimes, company tend not mind to its important of promotion and advertisement..”